Reflections on Gender and Diversity in Cross-Cultural On-line Teaching - Hanne Haaland (The Royal Danish Library, 2017)
This paper is based on the experiences of teaching gender and diversity applying a team based approach. The course ‘gender, culture and everyday life’ is taught as part of an online MA programme on Development Management to a group of international students from Europe, Africa, Asia, and Latin America. The underlying thinking in the course is that the cultural diversity of the students in terms of nationalities and their different every-day life experiences provide a good point of entry for discussing different understandings of gender roles and gender relations across cultures and social groups. In the course we try through the use of experience notes to encourage awareness of embodied and situated knowledge and to stimulate discussions that may move beyond general perceptions of gender relations in the field of development. We argue that students seem to struggle with transferring such experience-based knowledge into overall discussions and thus also struggle with escaping the confines of dominant narratives. Through examples from the course, we reflect on the use of experience notes in teaching gender, the strengths and weaknesses of a team based approach to teaching gender and diversity, as well as on our own positioning as lecturers in the field of gender and development.